2019
DOI: 10.21930/rcta.vol20_num1_art:1247
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del encalado en el uso eficiente de macronutrientes para cacao (Theobroma cacao L.) en la Amazonia colombiana

Abstract: En la Amazonia colombiana, el cultivo de cacao (Theobroma cacao L.) presenta bajo rendimiento debido a que la alta acidez del suelo limita el uso eficiente de nutrientes. Por lo tanto, esta investigación evalúa el efecto del encalamiento y la fertilización en un suelo ácido (Typic Udorthents) de la Amazonia colombiana sobre el uso eficiente de nutrientes (uen), en términos de la eficiencia agronómica (ea) y la eficiencia de recuperación del fertilizante (erf) para nitrógeno (N), fósforo (P) y potasio (K), y cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Few nutritional studies for cacao plants have been carried out to date. These studies show that certain genotypes can be more efficient in taking N, P, a n d K from the soil and respond differentially to fertilization programs, achieving in some genotypes optimal growth and high yields in production (Ribeiro et al, 2008;Puentes-Páramo et al, 2014b;Li et al, 2015;Cuenca-Cuenca et al, 2019;Rosas-Patiño et al, 2019). In the same line as these studies, Ofori et al (2017) demonstrated that several cacao genotypes have physiological differences that allow them to develop well in marginal conditions, with low irrigation and nutrient scarcity, managing to identify potential varieties for future genetic improvement programs; despite not determining nutritional efficiency.…”
Section: Nutritional Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Few nutritional studies for cacao plants have been carried out to date. These studies show that certain genotypes can be more efficient in taking N, P, a n d K from the soil and respond differentially to fertilization programs, achieving in some genotypes optimal growth and high yields in production (Ribeiro et al, 2008;Puentes-Páramo et al, 2014b;Li et al, 2015;Cuenca-Cuenca et al, 2019;Rosas-Patiño et al, 2019). In the same line as these studies, Ofori et al (2017) demonstrated that several cacao genotypes have physiological differences that allow them to develop well in marginal conditions, with low irrigation and nutrient scarcity, managing to identify potential varieties for future genetic improvement programs; despite not determining nutritional efficiency.…”
Section: Nutritional Efficiencymentioning
confidence: 99%
“…For cacao trees to grow appropriately and generate maximum productivity, plants must form a broad root system, with thick root and lateral roots found in the upper 20cm of the soil, which is the primary pathway for nutrient and water uptake (Hartemink, 2005).To establish a productive orchard in Colombia, it has been suggested to select soils with physical-chemical parameters close to those determined as appropriate for optimal crop development (Table 2, Table 3). It should be noted that these values may vary slightly depending on the edaphoclimatic conditions of each region, as well as the genotype sowed (Rosas-Patiño et al, 2019).…”
Section: Characteristics Of Cacao Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Morais (1998) determined that phosphorus is the nutrient that most limits production in Brazil. Rosas et al (2019) determined that the acidity of the soil of the Colombian Amazon is an adverse condition to reach maximum performance; however, they found that CCN-51 clone has greater ability in the use of nutrients. The same authors (Rosas et al 2017) pointed out that applications 7 Mg ha -1 of Mg(CO 3 ) 2 and Ca(CO 3 ) 2 allow a change in the pH of 4.36 to 6.0 in approximately two months, allowing an increase in the availability of nutrients.…”
mentioning
confidence: 99%
“…Increasing soil pH to pH > 6.0 not only decreases bean Cd, but decreases the degree of biomagnification of total soil Cd in the beans. Liming can chemically immobilize Cd and thus decrease availability to the cacao plant, while also providing co-benefits to cacao productivity by ameliorating acidity [85]. For example, a one-time application of lime to soils decreased cacao uptake of Cd by up to 1.7-fold [10].…”
Section: Synthesis and Conclusionmentioning
confidence: 99%